Electrochemical Arylation of Aldehydes, Ketones, and Alcohols: from Cathodic Reduction to Convergent Paired Electrolysis. Issue 13 (24th February 2021) - Zhang, Sheng; Li, Lijun; Li, Jingjing; Shi, Jianxue; Xu, Kun; Gao, Wenchao; Zong, Luyi; Li, Guigen; Findlater, Michael
Abstract: Arylation of carbonyls, one of the most common approaches toward alcohols, has received tremendous attention, as alcohols are important feedstocks and building blocks in organic synthesis. Despite great progress, there is still a great gap to develop an ideal arylation method featuring mild conditions, good functional group tolerance, and readily available starting materials. We now show that electrochemical arylation can fill the gap. By taking advantage of synthetic electrochemistry, commercially available aldehydes (ketones) and benzylic alcohols can be readily arylated to provide a general and scalable access to structurally diverse alcohols (97 examples, >10 gram‐scale). More importantly, convergent paired electrolysis, the ideal but challenging electrochemical technology, was employed to transform low‐value alcohols into more useful alcohols. Detailed mechanism study suggests that two plausible pathways are involved in the redox neutral α‐arylation of benzylic alcohols. Abstract : Electrochemical approaches to the direct arylation of carbonyls and alcohols through less‐explored cathodic reduction and convergent paired electrolysis are presented. This protocol features: excellent functional group (including ester, amide, amine, thioether, borate) tolerance, mild conditions (metal catalyst‐ and external reductant‐free), good scalability (>10 gram‐scale), and site‐selectivity.